Factors influencing thirst perception during the consumption of oral nutritional supplements in older adults. (March 2023) - Regan, E.; Feeney, E.L.; Hutchings, S.C.; O'Neill, G.J.; O'Riordan, E.D.
Highlights: Gap in the literature in relation to drivers of thirst with ONS consumption. Older adults had low salivary flow and were experiencing diminished thirst. Each ONS was hypertonic and those highest in protein had highest osmolality. Dentures and water consumption status influenced thirst and prospective water consumption. Physico-chemical properties of ONS did not impact thirst with ONS consumption. Abstract: Oral Nutritional Supplements (ONS) are often used as a strategy to aid nutrient adequacy in older adults. Research has highlighted that thirst increases with ONS consumption. This, combined with older adults' tendency for diminished thirst, may contribute to reduced ONS adherence. This study investigated how alterations in viscosity, protein content, and sweetness of ONS impact thirst perception after ONS consumption. Seventy-two older adults (mean age 71 ± 4 years, 27 men, 45 women) evaluated four ONS of varying protein contents, four ONS of varying sweetness, and four ONS of varying viscosities over three days, one day per ONS set. Each ONS was consumed over three sips (10 mL each). After three sips the panellists recorded their thirst, mouth-dryness, 'prospective water consumption', appetite (Visual Analogue Scales), and liking (9-point hedonic scale). Salivary flow was recorded at the start of each visit. ONS osmolality was also measured. Most panellists had diminished thirst and low salivary flow. Each ONS was hypertonic and those highest in protein had significantly higher osmolality. Thirst, mouth-drying, and 'prospective water consumption' were not significantly different following consumption of different ONS. Significant differences between cohort subgroups were observed. Non-denture wearers had higher ratings for 'prospective water consumption' compared to denture wearers. Those who needed regular reminders to drink water were significantly thirstier and had higher ratings for mouth-drying and 'prospective water consumption' than those who do not. Female panellists had lower liking for ONS, than males.